1983
DOI: 10.1093/carcin/4.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Induction of SCE by opium pyrolysates in CHO cells and human peripheral blood lymphocytes

Abstract: The induction of sister chromatid exchange (SCE) by opium pipe scrapings (sukhteh, Su) and the pyrolysis products of opium (Op) and of its major alkaloids, morphine (Mo), have been compared with that of cigarette smoke condensate (CSC). All pyrolysates induced SCE and the frequency was further increased by the inclusion of S9-mix in the protocol. The pyrolysates of Op induced considerably more SCE than CSC when the same concentrations were compared on a weight basis, and the rank in order of potency in CHO cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The epidemiological findings showing increased risk of several cancers with opium use are supported by laboratory studies showing that, after metabolic activation, opium dross has mutagenic activity in Salmonella typhimurium strains TA98 and TA100;30 causes frameshift mutations in S. typhimurium strains TA1538 and TA9829 and induces sister chromatid exchanges 31. These effects are mostly attributed to nitrogen-containing heterocyclic compounds derived from pyrolysis of morphine 32.…”
Section: Discussionmentioning
confidence: 93%
“…The epidemiological findings showing increased risk of several cancers with opium use are supported by laboratory studies showing that, after metabolic activation, opium dross has mutagenic activity in Salmonella typhimurium strains TA98 and TA100;30 causes frameshift mutations in S. typhimurium strains TA1538 and TA9829 and induces sister chromatid exchanges 31. These effects are mostly attributed to nitrogen-containing heterocyclic compounds derived from pyrolysis of morphine 32.…”
Section: Discussionmentioning
confidence: 93%
“…Some assays, such as GJIC and apoptosis can only be performed at very early passage of the primary culture, making widespread applicability more difficult. Cultured lymphocytes are frequently used to assess chromosomal aberrations, Comet, and SCE (68,265,266). …”
Section: Resultsmentioning
confidence: 99%
“…There are a lot of biochemical and physiological mechanism for relationship between opium consumption and risk of cancer (36,37). Studies have shown that opium pyrolysis and it alkaloids like morphine can result in mutagenicity, morphological changes and exchange sister chromatid in human lymphocytes (38).…”
Section: Discussionmentioning
confidence: 99%